(untitled) (XXI Century. Spanish Literature and Culture, 2024)
This article analyzes the migration experience of the poet and artist Dionisio Cañas as a queer man. His migration to New York in 1972, where he lived for more than three decades, allowed him to freely enjoy his non-normative sexuality, as well as to grow intellectually and professionally. At the same time, his poetry reveals a profound nostalgia for La Mancha, his native land, in addition to a critical view of the dehumanization in New York City. Upon his return to La Mancha in 2005, Cañas denaturalizes heteronormative national discourses to adopt a transnational identity that includes both Spanish and US realities, claiming that he feels like a nomad and that his home is not made up by one specific geographic place.